1992
DOI: 10.1016/0741-5214(92)90716-l
|View full text |Cite
|
Sign up to set email alerts
|

Axillopopliteal bypass for limb salvage

Abstract: Forty-one axillopopliteal bypass grafts have been placed in 30 patients for limb salvage in the past 12 years. The mean patient age was 65.6 years; 8 were women; 19 smoked; and six had diabetes. Sixteen grafts were straight axillopopliteal bypass grafts, and 25 were sequential axillopopliteal bypass grafts. Cumulative life-table primary patency rates at 1, 2, and 3 years were 70%, 56%, and 43%, respectively; secondary patency rates were 73%, 57%, and 50%, respectively. Corresponding limb salvage rates were 86%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Ascer et al [7] have reported a series of 55 cases of axillo-popliteal bypass with 5-year patency rate of 40 % and operative mortality rate of 8 %, Keller et al [8] have reported 41 cases with 3-year patency rate of 43 % and operative mortality rate of 20 %, Bastounis E et al [9] in their series of 67 cases of axillo-popliteal and axillodistal bypass have reported 5-year primary patency of 13 %, other series include less than 10 cases individually. Indications for axillo-popliteal bypass in these series were failed aortofemoral grafts, graft infection, and severe atherosclerotic Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Ascer et al [7] have reported a series of 55 cases of axillo-popliteal bypass with 5-year patency rate of 40 % and operative mortality rate of 8 %, Keller et al [8] have reported 41 cases with 3-year patency rate of 43 % and operative mortality rate of 20 %, Bastounis E et al [9] in their series of 67 cases of axillo-popliteal and axillodistal bypass have reported 5-year primary patency of 13 %, other series include less than 10 cases individually. Indications for axillo-popliteal bypass in these series were failed aortofemoral grafts, graft infection, and severe atherosclerotic Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Despite encouraging results achieved by some authors 11,14,36 in using the extra-anatomical femorofemoral or axillofemoral bypass as an inflow procedure, we reserve this approach only for very high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kram et al 16 presents a 78% five-year limb salvage rate after unilateral aortofemoropopliteal distal bypass. Keller et al, 36 presenting with 30 patients after axillopopliteal bypass, demonstrated a 69% limb salvage rate after three years. Ellenby et al 14 presented with a 77% limb salvage rate at five years in a group of 21 patients after femorofemoropopliteal bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospectively, in this patient, as the second operation, a supplementing extra-anatomical bypass grafting and resection of affected femoral artery with closure of the stumps should have been performed soon after recovery from shock condition, at the latest, within 7-10 days after the first operation, and a lateral femoral bypass or axillo-popliteal bypass grafting 10) could have been an appropriate procedure in this patient because extension of metastatic tumor to the obturator foramen was found on CT and during the operation.…”
Section: Discussionmentioning
confidence: 99%